PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PENGGUNA SEPEDAMOTOR SKUTIK HONDA SCOOPY DI SEMARANG - Yonanda Cambogie Army Maulana, 14.05.51.0101; Prabowo, Rokh Eddy (Students' Journal of Economic and Management, 2018)
This study analyzes the effect of product quality, price perception, and brand image on consumer satisfaction. The population in this study were users of Honda Scoopy scooter motorcycle in Semarang with a sample of 100 people. Primary data is processed with the help of the SPSS version 19 application program. The test results show that there is a positive and significant influence on product quality variables on consumer satisfaction and price perception on consumer aging, while brand image does not affect consumer satisfaction, because the positive is not significant. The ability of the three variables in explaining the customer satisfaction of users of Honda Scoopy scooter motorcycle is only 10.6 percent, the rest is determined by other variables such as service quality, trust, etc. Keyword : product qulality, price perception, brand image, and consumer satisfaction